Gradual and Transformative Institutional Change: the influence of stakeholders and advocacy coalitions at the Belo Monte Hydroelectric power plant - Vieira, Diego Mota (Organizações & Sociedade, 2021)
This work analyzes the performance of stakeholders and advocacy coalitions in processes of gradual institutional change based on the case study of the Belo Monte hydroelectric power plant. The methodology adopts content analysis, using shorthand notes of hearings held in the National Congress, and other publicly available documents. In-depth semi-structured interviews were also conducted, collecting data from individuals involved in the history of the power plant. The study allowed to characterize stakeholders pro or against the enterprise, observing their degree of influence and the role played. In addition, the work used the Advocacy Coalition Framework to verify how stakeholders formed three advocacy coalitions and exerted the strategies of institutional change ‘displacement,’ ‘conversion,’ and ‘layering’ following the gradual and transformative institutional change model. Empirical evidence indicates that the composition of coalition members may determine the type of institutional change and that institutional changes can also result from learning among coalitions, as the incorporation of socio-environmental considerations that have altered the original design of the hydroelectric power plant.